A liquid crystal ionomer-type electrolyte toward ordering-induced regulation for highly reversible zinc ion battery - Yuan, Du (2023)
Novel electrolyte is being pursued toward exploring Zn chemistry in zinc ion batteries. Here, a fluorine-free liquid crystal (LC) ionomer-type zinc electrolyte is presented, achieving simultaneous regulated water activity and long-range ordering of conduction channels and SEI. Distinct from water network or local ordering in current advances, long-range ordering of layered water channels is realized. Via manipulating water activity, conductivities range from ≈0.34 to 15 mS cm-1 , and electrochemical window can be tuned from ≈2.3-4.3 V. The Zn|Zn symmetric cell with LC gel exhibits highly reversible Zn stripping/plating at 5 mA cm-2 and 5 mAh cm-2 for 800 h, with retained ordering of water channels. The capability of gel for inducing in situ formation of long-range ordered layer SEI associated with alkylbenzene sulfonate anion is uncovered. V2 O5 /Zn cell with the gel shows much improved cycling stability comparing to conventional zinc electrolytes, where the preserved structure of V2 O5 is associated with the efficiently stabilized Zn anode by the gel. Via long-range ordering-induced regulation on ion transport, electrochemical stability, and interfacial reaction, the development of LC electrolyte provides a pathway toward advancing aqueous rechargeable batteries.